DESIGN STRUCTURE UNDER SEISMIC LOAD OF JABABEKA FILM INSTITUTE (BUILDING OF SCHOOL, WOMEN DORMITORY & MEN DORMITORY) WITH SPECIAL MOMENT RESISTING FRAME (SMRF) AS LATERAL FORCE RESISTING STRUCTURAL SYSTEM - SIONA TANA, ANGLIN
Film industry is one of 16 subsector which becomes the focus of development and management by Economy Creative Agency (BEKRAF RI). However, Indonesia is still lack of human resources who really have expertise in the field of film. Therefore, one of the solution to boost film industry in Indonesia is establish special school of film. This thesis discuss about the design structure under seismic load of JABABEKA Film Institute which consist of three main buildings : Building of School (seven floors), Building of Women Dormitory (eight floors) and Building of Men Dormitory (eight floors). This project is include in educational facilities category so that it has a building risk category = IV and earthquake primacy factor = 1,5. The design spectral acceleration parameters of this project are SDS = 0.567 g and SD1 = 0.352 g so that the seismic design category applied is KDS D. Based on the seismic design categories obtained, so “Special Moment Resisting Frame (SMRF) as Lateral Force Resisting Structural System” is used for the upper structure and “Dual System” is used for the lower structure (basement). In the stages of structural modeling, ETABS software is used for modeling Building of School, Building of Women Dormitory and Building of Men Dormitory. The results of the structural modeling are used in the stages of structural analysis such as the fulfillment of two-stage analytical procedure, checking for modal participating mass ratio, determining the natural period of the structure, determining the seismic response coefficient, determining static & dynamic shear forces, checking the seismic force scale, checking the interstory drift, checking the reinforcement ratio, checking the vertical delta, checking the P-Delta effect, determining the eccentricity & torque, checking the structural irregular, and checking the redundancy factor. Structural analysis conducted refers to SNI 1726 : 2012 on “Tata Cara Perencanaan Ketahanan Gempa untuk Struktur Bangunan Gedung dan Non Gedung”. After the stage of structural analysis is completed, then the process of structural detailing is conducted. The elements of the structure are secondary beam, primary beam, column, beam-column joint, plate, pile cap and tie beam. The process of structural detailing refers to SNI 2847 : 2013 on “Persyaratan Beton Struktural untuk Bangunan Gedung”. The software used in the process of structural detailing is pcaCOLUMN and SAFE.